2004
DOI: 10.1097/00002371-200411000-00030
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitor of the F1 Subunit of ATP Synthase (IF1) Modulates the Activity of Angiostatin on the Endothelial Cell Surface

Abstract: Angiostatin binds to endothelial cell (EC)-surface F 1 -F 0 ATP synthase, leading to inhibition of EC3 migration and proliferation during tumor angiogenesis. This has led to a search for angiostatinmimetics specific for this enzyme. A naturally occurring protein that binds to the F1 subunit of ATP synthase and blocks ATP hydrolysis in mitochondria is Inhibitor of F1 (IF1). The present study explores the effect of IF1 on cell surface ATP synthase. IF1 protein bound to purified F 1 ATP synthase and inhibited F 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In hepatocytes, surface ATPSβ serves as a receptor for ApoA-I or ApoE-enriched high-density lipoprotein 5–7. In ECs, ecto-ATPSβ binds to angiostatin, which suggests that the membrane-bound ATPS is involved in angiogenesis 810. Our previous study demonstrated that ECs incubated with cholesterol induced the translocation of ATPSβ from mitochondria to membrane caveolae,11 which suggests that ecto-ATPSβ may be involved in cholesterol efflux from the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocytes, surface ATPSβ serves as a receptor for ApoA-I or ApoE-enriched high-density lipoprotein 5–7. In ECs, ecto-ATPSβ binds to angiostatin, which suggests that the membrane-bound ATPS is involved in angiogenesis 810. Our previous study demonstrated that ECs incubated with cholesterol induced the translocation of ATPSβ from mitochondria to membrane caveolae,11 which suggests that ecto-ATPSβ may be involved in cholesterol efflux from the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…F 1 F 0 -ATP synthase is a mitochondrial protein; however, b-F1-ATPase, the F1 catalytic subunit of this enzyme, has been recently found to be present on the plasma membrane of various cell types, such as endothelial cells (25), neuronal cells (26), adipocytes (27), and hepatocytes (28). It is possible that this ecto-F1-ATPase can act as a cell surface receptor to which certain types of ligands can specifically bind.…”
mentioning
confidence: 99%
“…The positive control, piceatannol, was also a potent inhibitor, requiring ≤ 5 min of preincubation time for effective blocking. Other investigators have demonstrated inhibition of extracellular ATP synthesis by pretreatment of HUVECs for 30 min with much higher doses of angiostatin kringles 1–3 (K1–3) (50 μ m [35]) and piceatannol (1–20 μ m [33]; 500 μ m [35]) than those used here. As shown in Fig.…”
Section: Resultsmentioning
confidence: 93%